Cone Beam CT skeletal and nasomaxillary complex airway volume changes evaluation and correlation - Paola Pirelli; Valeria Fiaschetti; Aldo Giancotti; Roberta Condò; Gianluca Mampieri (Annali di Stomatologia, 2018)
Objective: evaluate the correlation between skeletal changes in 2D dimensions and volume changes of the upper airways before and after rapid maxillary expansion (RME) therapy in children with obstructive sleep apnoea (OSA) by Cone Beam computed tomography (CBCT) and between volume of the upper airways and clinical data.